Digest - Herfarth, Christian; Lehnert, Thomas (The British journal of surgery, 1998)
For this quarter's digest, Professor Christian Herfarth and Dr Thomas Lehnert have selected the best from the October to December 1997 issues of Der Chirurg. A digest for the BJS for the same period, written by Mr Colin Johnson, appears in the German journal.